THE CONCEPT OF MODALITY AND ITS MEANS OF EXPRESSION - Руденко, Наталія (Linguistic Bulletin (Movoznavchyi Visnyk), 2020)
Syntactic construction in its content and purpose is a formed act of thinking, so it not only reflects a specific situation of reality, but also conveys the attitude of the speaker to the expressed idea so has a certain author’s assessment of this reality. The category of sentence that is intended to make such connections is modality. In modern syntax, there has never been a consensus on the correlation of the category of modality with the semantic-grammatical, formal-grammatical or communicative level of the sentence, and also on defining the very concept of modality as a grammatical category. Purpose. We believe that it is important to determine the main directions of studying modality at all levels of the sentence – from formal grammatical to semantic and communicative. The article proposes a classification of modal values based on the analysis of the subjective perception of reality by the author of the statement. Results. A sentence is a complex unity of syntactic relationships, some of which are set between the syntactic construct and the ecclesiastical reality, and others within the sentence itself. The category that combines these levels is modality. Modality is a reflection of reality in the interpretation of the speaker, which reproduces this representation in a particular sentence. Modality does not belong entirely to the semantic-syntactic or communicative level of a sentence, but is a separate level of syntactic construction that interacts with other levels, but is not identical to them The modal level of the sentence, intended to convey the speaker’s attitude to what is said in the sentence, can be neither real nor unreal, since this message is expressed by the person, that is, his own, subjective vision of the situation, and on the other hand it is the statement is interpreted by the reader, that is, it is also subjective in nature. Therefore, it is worth considering modality not as objective / subjective, but according to the content that the speaker encloses in this message. The notion of modality with the meaning of realization / non-realization is connected with the concept of reality: what is depicted in the sentence is completely consistent with being as it is perceived by the subject. The formal expression of such a modality in a sentence is a predicate expressed by the verb. Modality with the meaning of possible / impossible (hypothetical or unrealistic modality) expresses the possibility or need for some action. The formal expression of such modality is the predicates expressed by the verbs of the subjunctive or imperative mood, as well as particles with a modal value of hypothetical or conventionality. The modal meaning of the desired / undesired conveys the desire, pleasure or dissatisfaction of the speaker, which is important for him / her. The formal expression of such a modality is the predicates expressed by verbs in imperative mood . The modal value of affirmation / denial (yes – no) confirms / denies the opinion expressed, the presence of some fact or phenomenon, and also confirms the speaker’s agreement with the message. The formal expression of this modality is yes or no. Originality. In the article modality is seen as an independent level of sentence, not part of the communicative or semantic level. Modality is an expression of the author’s vision of the world, its interpretation of reality, which he conveys to the addressee. Conclusion. Modality is an important category of syntax that provides a link between the semantic and communicative level of a sentence, forming an externally syntactic level of syntactic construction. It is an expression of the author’s, subjective vision of reality, so in its essence, it is a subjective category by value and consists of pairs of opposite meanings: desirability / undesirability, possibility / impossibility, realization / failure, objection / assertion, which in turn are shared into even smaller categories of values (possibilities -probability, hypotheticality, unreality, etc.).